2023
DOI: 10.3389/fimmu.2023.1077938
|View full text |Cite
|
Sign up to set email alerts
|

Orf virus DNA prime-protein boost strategy is superior to adenovirus-based vaccination in mice and sheep

Abstract: Contagious ecthyma (Orf), an acute and highly contagious zoonosis, is prevalent worldwide. Orf is caused by Orf virus (ORFV), which mainly infects sheep/goats and humans. Therefore, effective and safe vaccination strategies for Orf prevention are needed. Although immunization with single-type Orf vaccines has been tested, heterologous prime-boost strategies still need to be studied. In the present study, ORFV B2L and F1L were selected as immunogens, based on which DNA, subunit and adenovirus vaccine candidates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Furthermore, the F1L protein is involved in the adsorption and invasion of host cells by the virus ( 30 ). However, the B2L and F1L genes are highly conserved in ORFV and may not accurately reflect the true genetic characteristics of different ORFV strains ( 31 ). Phylogenetic analysis based solely on conserved genes may overlook genetic heterogeneity among ORFV strains ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the F1L protein is involved in the adsorption and invasion of host cells by the virus ( 30 ). However, the B2L and F1L genes are highly conserved in ORFV and may not accurately reflect the true genetic characteristics of different ORFV strains ( 31 ). Phylogenetic analysis based solely on conserved genes may overlook genetic heterogeneity among ORFV strains ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…F1L protein is the immunodominant envelope antigen of ORFV and participates in viral adsorption and entry of target cells (Czerny et al, 1997;Scagliarini et al, 2004). Several research groups have demonstrated the potential utility of the F1L protein as a candidate for subunit vaccines against various ORFV strains (Zhao et al, 2011;Wang et al, 2022Wang et al, , 2023. Considering the important roles played by F1L, it is essential to develop F1L mAbs and identify its antigenic epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-F1L antibody endpoint titers were measured via ELISA, as previously described, with modifications [9]. Briefly, MaxiSorp™ 96-well plates (Thermo Fisher Scientific, 430341) were coated with 1 µg/mL of purified F1L recombinant protein (Genscript, Piscataway, NJ, USA, custom production based on ORFV D1701 PP83 (ORFV059), residue 1-289) in 0.05 M carbonate buffer (pH9.0) overnight at 4 • C. After three washes with phosphate-buffered saline (PBS), the plates were blocked for 2 h in 200 µL/well of blocking buffer PBS-T (PBS, Tween20 0.05%) and 1% bovine serum albumin (BSA) (PAN-Biotech, P06-1391100) at 37 • C. The plates were subsequently washed three times with 300 µL/well of PBS-T, and serial dilutions of mouse serum in PBS-T (50 µL) were added to the wells and incubated for 2 h at 37 • C. After three washes with PBS-T, HRP-conjugated anti-mouse IgG-Fc fragment secondary antibody (Bertyl Laboratories, A90-131P) was incubated for 1 h at 37 • C. The plates were then washed five times with 200 µL/well of PBS-T and 50 µL/well of TMB substrate (BioLegend, 421101) added for 5 min in the dark.…”
Section: Humoral Response Against Orf Virus Protein F1l (Orfv059)mentioning
confidence: 99%